A comparative analysis of traffic impact assessment in the Philippines, Japan and South Korea implementation and the use of computer simulation as an analytical tool - Regidor, Jose Regin F. (Philippine Engineering Journal)
Traffic impact assessment (TIA) has become a necessity as cities and municipalities become aware of the potential impacts of new development on traffic flow. This paper compares the experiences of Japan and South Korea in the practice of TIA with that of the Philippines. The comparison is made with respect to their respective guidelines including the related laws and the TIA evaluation process followed in these countries. Four functions identified by the Institute of Transportation Engineers (ITE) are cited including forecasting and level of service analysis and the tools developed and employed in aid of these functions are discussed. Computer simulation is presented as an invaluable tool for the analysis of traffic impact and examples are used to illustrate the utility of simulation including a comparison of simulation models condensed from the Japanese guidelines. Finally, recommendations on the application or implementation of TIA in the Philippines are proposed.